BOSHLANG'ICH SINFLARDA MATEMATIKA O'QITISH METODIKASI (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article discusses the methodology of teaching mathematics in primary education. The importance of innovative and interactive teaching methods is highlighted, emphasizing how these can improve students' engagement and understanding of mathematical concepts. The article outlines various pedagogical strategies, including problem-based learning and visual aids, which can enhance the effectiveness of mathematics education in primary schools.